Advances in the molecular simulation and numerical calculations of the green high-energy oxidant ADN. (June 2022) - Lu, Qiangqiang; Chen, Fuyao; Xiao, Lei; Yang, Junqing; Hu, Yubing; Zhang, Guangpu; Zhao, Fengqi; Wang, Yinglei; Jiang, Wei; Hao, Gazi
Abstract: As a new green energetic oxidant, ammonium dinitramide (ADN) has excellent energy density and produces a low amount of combustion pollution, making it suitable for use in low-pollution solid propellants, space shuttle boosters, space transportation power systems and future strategic and tactical missiles. However, due to its strong hygroscopic properties, the development and applications of ADN have been hindered. To better understand, develop and use ADN, in practical applications, simulations and calculation methods have been proposed, which are efficient, economical and valid methods for studying the properties and potential applications of ADN. In this review, the literature on the simulation of ADN based on density functional theory (DFT), molecular dynamics (MD) calculations, the Monte Carlo (MC) method and numerical calculations is summarized. The research progress on the simulation and numerical calculation of ADN is systematically introduced from five directions: the simulation of the molecular properties of ADN molecules, the simulation of the thermal decomposition of ADN, the simulation of the ADN crystals and their modified ones, the simulation of the interaction between other molecules and ADN molecules, and the numerical simulation of ADN-based propellants used in engines/thrusters, with the aim of deepening the understanding of its basic characteristics, pyrolysis mechanism, MD characteristics and potential application potential of ADN, and providing theoretical support for basic research on this material and its practical applications. Graphical Abstract: ga1